Reinstatement of National Values in Primary Education in Nigeria: A Better Way to Attain National Integrity - Adelakun, Iyanuoluwa Samuel; Olorunsola, Edith Oluwafunmilola (Innovations in Pedagogy and Technology, 2025)
The continuous increase in moral decadence among Nigerian youths has raised serious concerns in recent times. Examination malpractice, internet fraud, money rituals, social vices, dishonesty, laziness, political and economic fraud are now the order of the day in some Nigerian primary schools. This is due to a lackadaisical attitude toward the teaching of national values in Nigerian primary schools. Shortage of funds, inadequately trained teachers, political instability, and the failure of supporting social organizations in upholding the teachings of national values in primary schools were also identified as challenges facing the implementation of national values in primary schools in Nigeria. If all these should persist, it may lead to the complete loss of national values in primary education and an unhealthy foundation. Nevertheless, this paper is a call for the restoration of national values in primary education in Nigeria to attain national integrity. A conceptual framework on the reinstatement of national values in primary education in Nigeria was designed to explain the interconnectivity between national values, primary education in Nigeria, and national integrity. For the sake of clarity, the study is grounded in Bertalanffy’s System Theory of 1968 that explains Nigerian primary school as a sub-system working towards the attainment of national integrity (Big System) through reinstatement of national values.